Aktivitas Ekstrak dan Tablet Nanopartikel Buah Okra (Abelmoschus esculentus (L) Moench.) Sebagai Anti- Dislipidemia Pada Tikus Yang Diberi High Fat Diet - Sarah Zaidan; Deni Rahmat; Ratna Djamil; Nadya Vresya Saputri (Fakultas Farmasi Universitas Pancasila, 2021)
Dyslipidemia is a condition caused by disruption of lipid metabolism due to the interaction of genetic factors and environmental factors. There is strong evidence of an association between LDL cholesterol and cardiovascular events based on clinical outcome studies, so LDL cholesterol is the main target in the management of dyslipidemia. In addition to using synthetic drugs, dyslipidemia can be treated by consuming natural ingredients, one of which is okra (Abelmoschus esculentus (L) Moench). The form of nanoparticles and nanoparticle tablets of okra fruit extract is an effort to increase antidyslipidemic activity and to make it easier to use. This study aims to obtain nanoparticle extracts and nanoparticle tablets of okra fruit extract which have antidyslipidemic activity in vivo against mice given the High Fat Diet (HFD). The research used 24 rats divided into 6 treatment groups, namely group I as normal control, group II as positive control using simvastatin as the control control, group III as a negative control, group IV as a control treatment of ethanol extract 70% okra fruit, group V as a control treatment of okra fruit extract nanoparticles, and group VI as a treatment of okra fruit extract nanoparticles tablets. All test substances are given for 14 days. Blood sampling was carried out on days 0, 14, and 28, with the parameters measured were lipid profiles including total cholesterol (KT), LDL, Triglycerides (TG) and HDL. 70% ethanol extract, extract nanoparticles, and okra fruit extract nanoparticle tablets can decrease KT levels by 33.14%, 46.31%, 45.42%, decrease TG levels by 39.46%, 43.56%, 41, 62%, decrease LDL levels by 45.22%, 68.76%, 59.94%, and can increase HDL levels by 103.80%, 119.20%, 114.39%. Based on the lipid profile of mice given HFD, 70% ethanol extract, nanoparticles, and okra fruit extract nanoparticle tablets had antidyslipidemic activity.